Domestic Violence in Africa: A Systematic Review of Concepts, Patterns, and Interventions - Anita Bans-Akutey (Goodwood Publishing, 2026)
Purpose: This systematic review employs domestic violence as an analytical lens to examine broader patterns, drivers, and responses to Gender-Based Violence (GBV) in African contexts. Research Methodology: Guided by established systematic review protocols, peer-reviewed journal articles were selected from major databases and screened using predefined inclusion and exclusion criteria. The review focused on studies addressing domestic violence in African countries, with attention to conceptual frameworks, socio-cultural and structural drivers, regional variations, and institutional responses. Data were extracted and synthesized thematically to identify recurring patterns, divergences across regions, and gaps in the literature. Results: The findings reveal that domestic violence in Africa is deeply embedded in gendered power relations, cultural norms, economic inequality, and weak institutional enforcement mechanisms. Significant regional variations emerge in the forms, prevalence, and social acceptance of domestic violence, shaped by differences in legal frameworks, kinship systems, and socioeconomic conditions. Although policy and legal reforms have expanded across many African countries, implementation gaps, limited survivor support services, and persistent social stigma continue to undermine effective prevention and response efforts in Africa. Conclusions: The persistence and prevalence of domestic violence across African contexts underscore deep-rooted gender hierarchies that reflect and reproduce wider patterns of inequality and violence. Limitations: The complexity and context-specific nature of domestic violence mean that generalized conclusions may not fully capture local variations in experience, reporting, and response. Contributions: This review offers an integrated and comparative perspective that moves beyond single-country or sector-specific analyses to a global perspective.